Investigations on electrochemical machining (ECM) of Al7075 material using copper electrode for improving geometrical tolerance. (2020) - Selvarajan, L.; Sasikumar, R.; Mohan, Dhanesh G.; Naveen Kumar, P.; Muralidharan, V.
Abstract: This research work focuses on electrochemical machining performance evaluation of Al7075 material ECM has become the most important and high precision technique in the manufacturing sector, since many intricate 3D profiles can be machined using a copper electrode. ECM process widely applied in aerospace industries using of multiple hole drilling, turbine blades within close limits and drilling jet engine turbine blades, etc. The objective of this experiment is found the maximum Material Removal Rate (MRR), reducing the machining time, good hardness and surface finish. The machining parameter considered were current (12 V), duty cycle (75%), and electrolyte concentration (32%). The performance measures such as metal removal rate (MRR), the machining time (min), hardness, form and orientation tolerance were examined. Main effect plot, interaction plot and contour plot analysis were used to optimize the process parameters for ECM processes. As a result, metal removal rate is maximized by increasing the electrolyte concentration (36 g/l), duty cycle (95%) and machining voltage (16 v). Metal hardness is improved by decreasing the machining voltage (12 V), duty cycle (75%) and increasing the electrolyte concentration (36 g/l). Minimum circularity is achieved at machining voltage, electrolyte concentration, and duty cycle are reduced. Minimum cylindricity is obtained while increasing the electrolyte concentration and decreasing the machining voltage. Minimum perpendicularity is achieved to increase of voltage and decrease of electrolyte concentration.